A highly active and stable La0.5Sr0.5Ni0.4Fe0.6O3-δ perovskite electrocatalyst for oxygen evolution reaction in alkaline media. (20th August 2017) - Wang, Cheng Cheng; Cheng, Yi; Ianni, Enrico; Jiang, San Ping; Lin, Bin
Graphical abstract: Highlights: A highly active and stable La0.5 Sr0.5 Ni0.4 Fe0.6 O3-δ perovskite electrocatalyst is developed for OER in alkaline media. The crystal structural details of La0.5 Sr0.5 Ni0.4 Fe0.6 O3-δ were quantified by synchrotron XRD quantification analysis. La0.5 Sr0.5 Ni0.4 Fe0.6 O3-δ delivered a higher intrinsic activity and stability than state-of-the-art Ba0.5 Sr0.5 Co0.8 Fe0.2 O3-δ . La0.5 Sr0.5 Ni0.4 Fe0.6 O3-δ is a new kind of cost-effective and high performance OER perovskite electrocatalyst. The simple doping strategy is a practical way to enhance oxygen evolution on perovskite electrocatalysts. Abstract: Owing to the slow kinetics of oxygen evolution reaction (OER), developing highly active and stable OER catalysts is of great importance to realize the industrial operation for water electrolysis, reversible fuel cells and so on. Here, we report a highly active and stable La0.5 Sr0.5 Ni0.4 Fe0.6 O3-δ perovskite electrocatalyst for OER in alkaline media. La0.5 Sr0.5 Nix Fe1-x O3-δ (LSNF) perovskites with different Ni/Fe ratio were synthesized by a typical sol-gel route and investigated as potential cobalt-free OER perovskite electrocatalysts. Synchrotron XRD quantification analysis was applied to quantify the crystal structural details and changes. La0.5 Sr0.5 Ni0.4 Fe0.6 O3-δ (LSNF-5546) materials show significantly higher intrinsic activities and better stability in 0.1 M KOH for the OER including onset potential (1.56 V) and Tafel slope (76 mV/dec), higher than that of other LSNF and state-of-the-art perovskite electrocatalyst Ba0.5 Sr0.5 Co0.8 Fe0.2 O3-δ (BSCF-5582). This work demonstrates that La0.5 Sr0.5 Ni0.4 Fe0.6 O3-δ (LSNF-5546) can be a new kind of cost-effective and high-performance perovskite electrocatalyst for OER in alkaline solution, and the simple doping strategy would be a practical way to enhance oxygen evolution on perovskite electrocatalysts.